Spectrophotometric Determination of Norepinephrine in Industrial Equipment Cleaning Rinse Water by Its Own Absorbance and The Tollens’ Reagent - Anatolyevich Nikolaychuk, Pavel (Universitas Islam Indonesia, 2024)
A literature review of the available spectrophotometric methods of determination of catecholamines is presented. Based on this review, two simple spectrophotometric methods for the determination of norepinephrine bitartrate in pharmaceutical formulations and industrial equipment cleaning rinse waters were chosen and validated. The first method for the determination of norepinephrine at ppm levels utilizes the absorbance band of the solution of norepinephrine bitartrate at 279 nm. The second method for the determination of norepinephrine at ppb levels is based on the reaction of norepinephrine with the Tollens’ reagent in the presence of the cationic surfactant cetylpyridinium chloride and the colorimetric determination of the formed colloidal silver nanoparticles. The calibration graphs are linear in the range from 1 to 150 mg/l of norepinephrine for the first method and 25 µg/l to 10 mg/l for the second method. The molar attenuation coefficients are 388 and 7560 m2/mol, respectively, the limits of detection are 1.1 mg/l and 3.1 µg/l, and the limits of quantification are 3.3 mg/l and 9.4 µg/l, respectively. Both methods are selective concerning the common excipients, show good accuracy (the relative uncertainties do not exceed 4 and 7%, respectively) and precision (the relative standard deviations do not exceed 4 and 7%, respectively), and do not require lengthy sample preparation and sophisticated laboratory equipment.